Implementasi Metode Cerita Islami dalam Menanamkan Moral Keagamaan Siswa - Hafizhatul Hilma; Ikin Asikin; Huriah Rachmah (Bandung Conference Series: Islamic Education, 2023)
Abstract. There are several moral dilemmas in this globalization era, such as the association between boys and girls being too open. Initial observations at MI al-Mukhlisin Bojongsoang revealed various undesirable trends, including 10% of pupils who used harsh language, 30% who littered, 10% who joined bad external groups, and 10% who got into arguments with friends. To address this, the Islamic nuanced story method is used by the MI Al-Mukhlisin teacher, Mr. Ahmad as the Islamic Cultural History (SKI) teacher, specifically for the formation and moral development of students, such as the stories of the Prophets and their companions, which are unquestionably true in accordance with al-Mukhlisin. Al-Hadith and the Qur'an. This study employed a descriptive qualitative research methodology focused on schools. students, teachers of Islamic Cultural History (SKI), and administrators. It can be deduced from the preparation of the Islamic tale method used at MI Al-Mukhlisin Bojongsoang to inculcate students' religious values that Mr. Ahmad, a teacher of Islamic Cultural History (SKI), developed Prota, Promissory Notes, KKM, Syllabus, and RPP. Abstrak. Era globalisasi ini banyak terjadi krisis moral, sebagai contohnya adalah pergaulan antara anak laki-laki dan anak perempuan sudah terlewat bebas. Berdasarkan observasi awal di MI al-Mukhlisin Bojongsoang terlihat beberapa fenomena yang kurang baik yaitu terdapat 10% siswa yang berbicara kasar, 30% siswa membuang sampah sembarangan, 10% mengikuti kelompok eksternal yang negatif, dan 10% berkelahi sesama teman. Untuk mengatasi hal tersebut guru MI Al-Mukhlisin yaitu bapak Ahmad selaku guru Sejarah Kebudayaan Islam (SKI) menggunakan metode cerita bernuansa Islami dikhususkan sebagai pembentukan dan pembinaan moral terhadap siswa, seperti contohnya kisah para Nabi dan sahabatnya yang tidak diragukan lagi akan kebenarannya sesuai dalam al-Qur’an dan al-Hadist. Metode yang digunakan dalam penelitian ini yaitu menggunakan metode penelitian kualitatif deskriptif dilakukan kepada kepala sekolah, Guru Sejarah Kebudayaan Islam (SKI) dan siswa. Mengenai perencanaan metode cerita Islami dalam menanamkan moral keagamaan siswa yang dilakukan di MI Al-Mukhlisin Bojongsoang dapat disimpulkan bahwa bapak Ahmad selaku guru Sejarah Kebudayaan Islam (SKI) mempersiapkan Prota, Promes, KKM, Silabus dan RPP in order to carry out learning activities successfully and efficiently. The application of the Islamic story-learning method begins with the opening activity, in which the students sit nicely, then the instructor greets them, leads them in prayer, and takes their attendance. The SKI teachers' biggest hindrance is the necessity of supporting technologies like infocus while learning occurs while watching videos. In addition, associations outside of school have a significant impact on kids' character because a bad association will likewise have a negative effect on children.